Assistance of Productive Business Efforts to Support Marketing in EmhadeColection Mayong by Using the Online Shop Application - Setiawan, Deni; Amirotunnisa; Efendi, Abdullah (Jurnal Pengabdian kepada Masyarakat Khaira Ummah, 2023)
EM HA DE Collection is a sewing convection that only sews school uniforms, besides that EM HA DE Collection does marketing in the traditional way or word of mouth. From this, the UNISNU Jepara XIV KKN Team in Pelemkerep 1 Village assisted and socialized convection owners to make new products other than school uniforms so that the idea emerged to make t-shirts. In addition, in handling marketing issues, assistance is carried out in creating an online shop account that uses shopee as marketing. Only need a gadget or smartphone from the owner to be able to run online marketers using shopee. So that the target achieved is to increase the sales turnover of EM HA DE collection in a short time.